Penerapan Sistem RAS untuk Peningkatan Kualitas Air Budidaya Ikan Patin di Pondok Pesantren Nurul Muhibbin Halong, Kalimantan Selatan - Fatanul Thoriq; Wiyoto Wiyoto; Andri Iskandar; Imza Hermawan (Institut Pertanian Bogor, 2025)
The Nurul Muhibbin Halong Islamic Boarding School is a boarding school in South Kalimantan with an Asian catfish cultivation business unit managed by students. This unit has not been managed well, as can be seen from the students' lack of understanding in carrying out cultivation, which has an impact on the poor quality of the cultivation pond water. The aim of this activity was to improve water quality through a recirculating aquaculture system (RAS). Training and implementation of the RAS system. The results of this activity show that the implementation of the RAS system makes water quality more controlled with dissolved oxygen ranging from 0,75±0,32–5,13±0,80 mg/L, pH ranging from 4,78±0,24–7,14±0,72, temperature in the range of 27,9± 0,64–32,7±0,27°C, and ammonia 0,25 mg/L. The implementation of RAS can improve water quality to be much better and is in line with production performance, especially fish survival and growth.